2008
DOI: 10.2337/dc07-1750
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Glucokinase Gene of the Fetus Result in Reduced Placental Weight

Abstract: OBJECTIVE -In human pregnancy, placental weight is strongly associated with birth weight. It is uncertain whether there is regulation of the placenta by the fetus or vice versa. We aimed to test the hypothesis that placental growth is mediated, either directly or indirectly, by fetal insulin.RESEARCH DESIGN AND METHODS -Birth weight and placental weight were measured in 43 offspring of 21 parents with mutations in the glucokinase (GCK) gene (25 had inherited the mutation and 18 had not), which results in reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 21 publications
2
15
0
2
Order By: Relevance
“…A C C E P T E D ACCEPTED MANUSCRIPT 16 (26). There was no difference in placental weight in both the GCK N/N and GCK N/M groups between those treated with insulin and those not treated with insulin (680 g vs 680g, respectively, p=0.69)…”
Section: A N U S C R I P Tmentioning
confidence: 79%
“…A C C E P T E D ACCEPTED MANUSCRIPT 16 (26). There was no difference in placental weight in both the GCK N/N and GCK N/M groups between those treated with insulin and those not treated with insulin (680 g vs 680g, respectively, p=0.69)…”
Section: A N U S C R I P Tmentioning
confidence: 79%
“…It can stimulate (1) placental growth and also growth of the fetal heart, at least in non-human primates [29,30], (2) glycogen deposition in the placental endothelium (Desoye, Hiden unpublished) and (3) aerobic fetal metabolism. The latter will raise the demand for oxygen in the fetus.…”
Section: The Fetal Phenotype In Diabesitymentioning
confidence: 96%
“…Velho et al has been arisen the importance of the mutation inheritance by the foetus [91] who demonstrated that a maternal mutation of MODY2 diabetes results in increased birth weight while a foetal mutation leads to reduced birth weight. Furthermore, Shields et al [92] reported reduced placental weight in mutation-carrying offspring as a result of reduced foetal insulin secretion while Spyer et al [93] showed increased foetal weight without restoration of the weight to normal by maternal insulin treatment. Additionally, the HNF4A maternal polymorphism has been associated with increased birth weight and, in some cases, with transient neonatal hypoglycaemia due to foetal hyperinsulinaemia while a dual opposite role in the b-cell activity during different periods of life has been proposed for this mutation [94].…”
Section: Pregnancy Outcome and Response To Treatmentmentioning
confidence: 97%